Bereavement and Transformation: A Psycho-spiritual and Post-traumatic Growth Perspective - Bray, Peter (Journal of religion and health, 2013)
In the aftermath of loss, it is not uncommon for individuals to disclose psycho-spiritual experiences that lead to personal changes and psychological growth. This article argues for and outlines a broad conceptual framework that captures and acknowledges the significance of these subjective experiences. The model synthesises and integrates two approaches to healthy growth: Lawrence Calhoun and Richard Tedeschi's post-traumatic growth model and Stanislav and Christina Grof's model of psycho-spiritual transformation. A rationale for a broader model and underpinning theory is briefly discussed, and their shared understandings about the human potential for growth in the struggle through loss are explored.